The Influence of Work Environment and Position Promotion on Job Satisfaction of BPN West Aceh Employees - Riana Wandira; Ivon Jalil (Ridwan Institute, 2021)
This survey was conducted at the BPN Aceh Barat Office located on Jl.Swadaya, Meulaboh, Aceh Barat. With the aim of discovering the consequences of environmental conditions and the promotion of job satisfaction for BPN Aceh Barat personnel. In the population survey, all personnel of the BPN Aceh Barat totaled 37 people. Determination of the sample using the saturated sampling method with all the population being sampled, so the number of samples in this survey is 37 people. In this survey, the researcher applies an associative quantitative design. Materials are obtained by distributing questionnaires in the form of questions to be answered by the respondents. The data analysis used multiple linear regression analysis. The source of the data comes from primary data, the data is obtained directly from the respondents. The results of this survey prove that the environment and promotions, either partially or simultaneously, have a positive and significant influence on employee satisfaction at the BPN Aceh Barat Office. With the results of the determinant coefficient being able to explain the Environment and Promotion of Employee Satisfaction as much as 64.5%, the remaining 35.5% was obtained from other factors and was not examined in this survey model.